Covid-19 in Children and Young Adolescents in Al Ain, United Arab Emirates- a Retrospective Cross-Sectional Study - Elghoudi, Ahmed; Aldhanhani, Huda; Ghatasheh, Ghassan; Sharif, Elsadeq; Narchi, Hassib (Frontiers in Pediatrics, 2021)
Aim: The aim of this study is to estimate the age-specific prevalence of COVID-19 in children admitted to our hospital in Al Ain City, United Arab Emirates, to describe their clinical features, diagnostics, treatment required and outcomes and to compare our findings with similar reports in the literature. Patients and Methods: We reviewed the electronic patient records of all the children managed in Al Ain hospital within 1st March and 31st May 2020 with confirmed COVID-19 (ICD-10 code U07.1). Al Ain hospital, is the designated COVID-19 Centre in the city. Results: There were 288 children admitted with a confirmed diagnosis of COVID-19 during the study period (mean age 7.3 years, median 6.5, range 1 month to 16.9 years). The age-specific point prevalence was the highest under the age of five years (mean 2.0 per 1,000, 95% CI 1.7, 2.4) and decreased progressively to 0.6 per 1,000 (95% CI 0.4, 0.9) over the age of 14 years. Hospital admission was required for 193 (67%) children while 95 (33%) were discharged from the Emergency department. Most children (n=214, 74%) had been exposed to a family member with suspected or confirmed COVID-19 and asthma was the most frequent comorbidity (n=37, 13%). The most common symptoms were cough (n=130. 45%), fever (n=14, 4.8%), upper respiratory tract infection (n=93, 10.8%) and lower respiratory tract infection in 28 (9.7%). None of the children presented with acute respiratory distress syndrome, neurological symptoms, sepsis or septic shock. Neutropaenia (absolute neutrophil count or ANC< 1.5 x 109/L) was observed in 10.4% and thrombocytopaenia (<150 platelets x 109/L) in 72% of children. Nineteen patients (9%) had abnormal imaging studies (chest X-ray and chest computed tomography). Abnormalities were bilateral in six (43%), right-sided in seven (50%) with only one child (7%) with left-sided involvement. None of the children required invasive respiratory support, but four (1.4%) required non-invasive respiratory support. The median length of hospital stay was 3.3 days [1.9, 5.9]. There were no deaths in the hospital even in those with comorbidities.